Climate Resilient Green Economy Strategy: Sector-wise GTP II Implementation Monitoring Checklist - Bayleyegn, Debasu; Ericksen, Polly J.; Solomon, Dawit (2018)
Poverty eradication through broad-based accelerated and sustained growth is outlined in the Growth and Transformation Plan (GTP). Through Agricultural Development-Led Industrialization (ADLI), the country aims to build an economy with a modern and productive agricultural sector and a strong industrial sector, ultimately increasing per capita income to the level of middle-income countries by 2025. Achieving these ambitious objectives is challenging, but vital for the future of Ethiopia and its citizens. Climate change is one of the major current challenges and adds considerable stress to the societies and environment. From shifting weather patterns that threaten food production to rising sea levels that increase the risk of catastrophic flooding, the impacts of climate change are global in scope and unprecedented in scale. Ethiopia has historically suffered from climatic variability. Repeated rain failures, famines and chronic food crisis resulting from frequent droughts, environmental degradation, and decline in food production have rocked the country many times and remain a major challenge. The country’s economic output growth is closely linked to fluctuations in precipitation levels, as its agriculture is highly rain-fed, with only 2% of total arable land covered by irrigated and permanent crops. This strong association between rainfall and the economy is largely due to the nature of the country’s most dominant sector, agriculture and weak capacity of the rural population to adapt to climate variations.